Clarifying the Content Coverage of Differing Psychopathy Inventories through Reference to the Triarchic Psychopathy Measure - Drislane, Laura E. (2013)
The Triarchic Model of psychopathy (Patrick, Fowles, and Krueger, 2009) was formulated as an integrative framework for reconciling differing conceptions of psychopathy. The model characterizes psychopathy in terms of three distinguishable phenotypic components: boldness, meanness, and disinhibition. Data from a large mixed-gender undergraduate sample (N = 618) were used to examine relations of several of the best-known measures for assessing psychopathic traits with scores on the Triarchic Psychopathy Measure (TriPM), an inventory developed to operationalize the Triarchic Model through separate facet scales. Analyses revealed that established inventories of psychopathy index components of the model as indexed by the TriPM to varying degrees. While each inventory provided effective coverage of meanness and disinhibition components, instruments differed in their representation of boldness. Current results demonstrate the heuristic value of the Triarchic Model for delineating commonalities and differences among alternative measures of psychopathy, and provide support for the utility of the Triarchic Model as a framework for reconciling alternative conceptions of psychopathy.